New analysis finds pandemic didn’t dampen deforestation - Villarino, Maria Eliza J. (CGIAR System Organization, 2022)
Despite the massive upheavals in the first year of the COVID-19 pandemic, deforestation globally proceeded more or less as expected from the trends established over the last 15 years, according to a recent study from researchers at the Alliance of Bioversity International and CIAT. In the paper “Has global deforestation accelerated due to the COVID-19 pandemic?” published in mid-November 2022, the researchers used historical deforestation data (2004–2019) from the Terra-i pantropical land cover change monitoring system to project expected deforestation trends for 2020.